China's Non-Western Soft Power Policy In Establishing A New Order: A Review Of Strategy And Resources - Ali, Hemn Shawkat (Universitas Islam Negeri Raden Intan Lampung, 2023)
State power, in the modern era, is not just based on the concepts of political, military, and economic efficiency. The rise of the era of globalization and the interaction and interdependence of state in the international system has led to the centralization of a new concept known as